Sistem Manajemen Keuangan Berbasis Website Dengan Metode Agile - Endang Retnoningsih; Yunus Fadhillah Soleman; M. Dicky Nur Setya Azi (LPPM Universitas Bina Sarana Informatika Kampus Kabupaten Banyumas, 2025)
Every company has regulations in formulating policies related to financial decisions. To minimize risks, financial management must be carried out carefully and thoroughly. Therefore, companies require a dedicated financial management system to support decision-making processes. At PT. Awang Sejahtera Permai (ASP), financial management is currently conducted using Ms. Excel and Zahir application. However, as the company expands and manages multiple business units, there is a need for a financial management system that can accommodate the company’s growing requirements. Hence, this research develops a web-based system to manage cash flow, sales, and financial reports. The system development was carried out using the Agile method. The results of the study indicate that the implementation of the web-based financial management system has a positive impact by integrating cash flow data, sales, and company financial reports.